Coup Government of Afghanistan From the Perspective of Islamic Constitutional Law - Sadzali, Ahmad; Madjidah, Durriyatul Afiqoh Uzma (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
The Taliban are currently in control of the government in Afghanistan after taking over the authority from President Ashraf Ghani. The takeover is classified as a government coup because it was not conducted under the Afghan Constitution. Departing from this issue, this normative research examines the background of the Afghan government coup d’etat and analyzes it from the Islamic Constitutional Law perspective. The result concludes that (1) the coup of the Afghan government by the Taliban was triggered by the withdrawal of US troops from Afghanistan as a follow-up to the Doha agreement made between the United States and the Taliban. After the Taliban succeeded in occupying several areas, including the capital city of Kabul, Ashraf Ghani fled from Afghanistan to the United Arab Emirates, causing the collapse of the government; and (2) from the perspective of Islamic Constitutional Law, the Afghan government coup can be viewed from (a) the obligation to comply with the constitution, and (b) post-coup benefit considerations. Keywords: goverment; coup de etat; Islamic constitutional law.